Inhibition of c‐Jun N‐terminal kinase activation reverses Alzheimer disease phenotypes in APPswe/PS1dE9 mice. Issue 4 (2nd March 2015) - Zhou, Qiong; Wang, Man; Du, Ying; Zhang, Wei; Bai, Miao; Zhang, Zhuo; Li, Zhuyi; Miao, Jianting
Abstract : Objective: Growing evidence indicates that the activation of c‐Jun N‐terminal kinase (JNK) is implicated in the multiple major pathological features of Alzheimer disease (AD). However, whether specific inhibition of JNK activation could prevent disease progression in adult transgenic AD models at moderate stage remains unknown. Here we first investigated the potential disease‐modifying therapeutic effect of systemic administration of SP600125, a small‐molecule JNK‐specific inhibitor, in middle‐aged APPswe/PS1dE9 mice. Methods: Using behavioral, histological, and biochemical methods, outcomes of SP600125 treatment on neuropathology and cognitive deficits were studied in APPswe/PS1dE9 mice. Results: Compared with vehicle‐treated APPswe/PS1dE9 mice, chronic treatment of SP600125 for 12 weeks potently inhibited JNK activation, which resulted in a marked improvement of behavioral measures of cognitive deficits and a dramatic reduction in amyloid plaque burden, β‐amyloid production, tau hyperphosphorylation, inflammatory responses, and synaptic loss in these transgenic animals. In particular, we found that SP600125 treatment strongly promoted nonamyloidogenic amyloid precursor protein (APP) processing and inhibited amyloidogenic APP processing via regulating APP‐cleavage secretase expression (ie, ADAM10, BACE1, and PS1) in APPswe/PS1dE9 mice. Interpretation: Our findings demonstrate that chronic SP600125 treatment is powerfully effective in slowing down disease progression by markedly reducing multiple pathological features and ameliorating cognitive deficits associated with AD. This study highlights the concept that active JNK actually contributes to the development of the disease, and provides critical preclinical evidence that specific inhibition of JNK activation by SP600125 treatment may be a novel promising disease‐modifying therapeutic strategy for the treatment of AD. Ann Neurol 2015;77:637–654